2023
DOI: 10.1161/hypertensionaha.123.21084
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Urine Biomarkers of Kidney Tubule Health With Incident Hypertension and Longitudinal Blood Pressure Change in Middle-Aged Adults: The CARDIA Study

Abstract: BACKGROUND: Urine biomarkers of kidney tubule injury associate with incident hypertension in older adults with comorbidities, but less is known about these associations in younger adults. METHODS: In 1170 participants of the CARDIA study (Coronary Artery Risk Development in Young Adults; mean age, 45 years; 40% Black people; 56% women) without hypertension, cardiovascular disease, or kidney disease at baseline, we examined associations of urine MCP-1 (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…Two cohort studies have reported that urinary KIM1 was not associated with incident hypertension. 33 , 34 In contrast, our present study observed strong positive associations of plasma KIM1 with SBP and hypertension, which is consistent with several cross-sectional studies that have demonstrated positive associations of plasma/serum KIM1 with BP and hypertension. 35 37 The difference in biosamples used to measure KIM1 may partially explain these distinct findings.…”
Section: Discussionsupporting
confidence: 92%
“…Two cohort studies have reported that urinary KIM1 was not associated with incident hypertension. 33 , 34 In contrast, our present study observed strong positive associations of plasma KIM1 with SBP and hypertension, which is consistent with several cross-sectional studies that have demonstrated positive associations of plasma/serum KIM1 with BP and hypertension. 35 37 The difference in biosamples used to measure KIM1 may partially explain these distinct findings.…”
Section: Discussionsupporting
confidence: 92%
“…In this same group of participants from the CARDIA cohort, we previously found that lower urine EGF levels were uniquely and independently associated with a higher risk of incident hypertension. 35 In combination with our current findings, this work in CARDIA might suggest that early reductions in kidney tubule function may have a causal role in the development of both hypertension and CKD in parallel.…”
Section: Discussionsupporting
confidence: 80%